Effects of Depression and Antidepressant Use on Cognitive Deficits and Functional Cognition Following Severe Traumatic Brain Injury. Issue 6 (November 2016) - Failla, Michelle D.; Juengst, Shannon B.; Graham, Kristin M.; Arenth, Patricia M.; Wagner, Amy K.
Abstract : Objective: To use a Rehabilomics framework to evaluate relations hips between post–traumatic brain injury (TBI) depression (PTD) and potential associated factors, including antidepressant use, on cognitive recovery following severe TBI. Participants: Severe TBI survivors ( n = 154), recruited from a level 1 trauma center. Design: Prospective cohort study with assessments at 6 and 12 months postinjury. Main Measures: Patient Health Questionnaire-9 (PTD symptoms); cognitive composite score from a neuropsychological assessment battery (cognitive impairment); and Functional Independence Measure–Cognition (FIM-Cog, self-reported functional cognition). Results: Individuals with and without PTD did not differ with respect to cognitive impairment. However, antidepressant use, regardless of PTD status, was associated with cognitive impairment. Individuals with PTD reported lower FIM-Cog scores at both time points compared with those without PTD. In a post hoc longitudinal analysis, individuals with late-onset PTD had worse cognitive impairment. Conclusion: These results suggest that antidepressant use impairs cognition among individuals without PTD. Also, PTD did not directly affect cognitive impairment but may affect functional cognitive limitations through self-evaluation and apathy/motivation factors. Abstract : Supplemental Digital Content is Available in the Text.